Effects of calcium or sodium ions on the properties of whey protein isolate-lotus root amylopectin composite gel. (February 2019) - Liu, Kang; Li, Qiang-Ming; Zha, Xue-Qiang; Pan, Li-Hua; Bao, Li-Juan; Zhang, Hai-Lin; Luo, Jian-Ping
Abstract: The aim of this study was to investigate the effects of Ca 2+ and Na + on the properties of whey protein isolate (WPI)-lotus root amylopectin (LRA) composite gel system. Results showed that an appropriate concentration of these two salt ions can induce the formation of WPI-LRA composite gel. Compared to the gel with free of Ca 2+, the gel strength, water holding capacity and thermal transition temperature were enhanced by 2.2-fold, 3.4% and 1.9 °C, respectively, when 0.1 M CaCl2 were added to the gel system. With respect to Na +, 0.05 M was found to be an appropriate dosage for the formation of WPI-LRA composite gel. Under this concentration, the gel strength, water holding capacity and thermal transition temperature were enhanced by 2-fold, 2.2%, 2.8 °C, respectively. The storage modulus of WPI-LRA was changed by the addition of Ca 2+ or Na + . The analysis of scanning electron microscopy revealed that both Ca 2+ at 0.1 M and Na + at 0.05 M induced a compact and stable network of WPI-LRA composite gels. In addition, the measurement of reactive sulfhydryl group (SH) content and Fourier transform infrared spectroscopy were performed to investigate the gel formation mechanism induced by the two salt ions. Results indicated that the increase in the contents of SH, the changes in the protein as indicated by the relative peak areas of amide II band might be the main reason for ion-induced formation of WPI-LRA composite gel. These results obtained in the present work will provide valuable evidences for the utilization of WPI-LRA composite gels in food industry. Graphical abstract: Image 1 Highlights: Textural properties of WPI-LRA gels were enhanced by 0.1 M Ca 2+ or 0.05 M Na + . Rheological properties of WPI-LRA gels were improved by 0.1 M Ca 2+ or 0.05 M Na + . Compact network of WPI-LRA gels were induced by 0.1 M Ca 2+ or 0.05 M Na + . The reactive -SH of WPI-LRA gels was increased by 0.1 M Ca 2+ or 0.05 M Na + . Peak area of amide II band of WPI-LRA gels was increased by 0.1 M Ca 2+ or 0.05 M Na + .